Nutritional composition and phytochemical content of wild edible tuber (amorphophallus abyssinicus) crop - Eden Genetu Tsehay; Shimelis Admassu Emire; Habtamu Admassu; Teshome Assefa Gebeyehu (International Journal of Food Properties)
There are various neglected and underutilized tuber crops grown in Ethiopia with remarkable nutritional potential, the most prominent being Amorphpohallus abyssinicus. The study aimed to evaluate the nutritional composition, functional property, and phytochemical contents of two cultivars of A. abyssinicus (locally termed as Hambaguyta, and Bagana). Results of the study showed that the two cultivars significantly (p ≤ .05) differ in moisture (11.51%, 9.11%), ash (2.64%, 3.6%) and crude fiber (1.46%, 2.42%) contents for hambaguyta and bagana, respectively. The cultivars were found to possess high carbohydrate (79.37% and 79.15%) and low lipid (0.47%, 0.47%) contents. In terms of mineral composition, calcium was found to be abundant in both cultivars. Bagana tuber has shown higher contents of magnesium (25.19 mg/100 g), Zinc (4.74 mg/100 g), and phosphorus (176.85 mg/100 g) than hambaguyta. However, heavy metals, including lead, arsenic, and mercury were below their detection limits. Phytochemicals: phytate, tannins, oxalate, cyanide, and polyphenols such as total phenol and flavonoid were determined for both cultivars. Good water absorption and low oil absorption capacities were also recorded for the two cultivars. Generally, this study can provide valuable information about these two cultivars as they have ample potential for the application of food and food-related product development.